Effectiveness of My Alazka Application Learning Media in Improving Student’ Chemistry Learning Outcomes - Wahjusaputri, Sintha; Ramadhani, Siti Sarah; Saepudin, Asep; Reihan, Muhammad; Suryanto, Hendi (JPPS (Jurnal Penelitian Pendidikan Sains), 2023)
Objective: This research aims to determine, analyze, and identify the effectiveness of the My Alazka Application learning media on the chemistry learning outcomes of 10th grade pupils. Method: This study used a quantitative method for experimental research. The subject of this study was a 28 Student in 10th grade, in accordance to the pretest-posttest design with a single group. This research uses instruments such as questionnaires that are used once before the investigation, known as the pre-test, and once after the experiment, known as the post-test. Result: Based on the Descriptive N-Gain Score data output, The data indicates the mean N-Gain score among students in 10th grade is 63.3074 or 0.63 which is included in the "moderate".  The use of My Alazka can significantly enhance the effectiveness of the learning process in communicating messages and lesson content, also learning outcomes of chemistry subjects for student in 10th grade. Novelty: My Alazka application can be an alternative solution for educators and students during the implementation of the learning processes to improve chemistry learning outcomes for 10th grade student.